Analisa Perilaku Konsumen Kopi di Kabupaten Bondowoso dan Implikasinya Terhadap Strategi Pemasaran Kopi Java Ijen Raung Kabupaten Bondowoso - Doktri, Weni Indah (Proceedings of Annual Conference on Community Engagement, 2018)
Bondowoso Regency is the best Arabica coffee producing district in Indonesia, known as Kopi Java Ijen Raung, but the coffee consumed is not Kopi Java Ijen Raung but other processed coffee. This phenomenon certainly requires the Java coffee agroindustry Ijen Raung to develop coffee products to be more acceptable to coffee consumers in Bondowoso. An information about consumer behavior is needed by analyzing the characteristics and factors that influence coffee purchasing decisions, making it easier for Kopi Java Ijen Raung to determine its marketing strategy. The results showed that consumers coffee factors that influence coffee purchasing decisions are personal and psychological factors, product attribute factors, cultural factors, social and external consumer environment, viscosity factors and non-product attribute factors.